Labour market stability in a zero-growth economy - Valeria Jimenez (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2023)
Although traditionally post-Keynesians tackle unemployment issues through the stimulation of aggregate demand, boosting demand indefinitely is no longer possible if we consider environmental constraints. In fact, according to several ecological economists, meeting the environmental targets of the Paris Agreement will involve a halt in economic growth or even degrowth. Within this context, important interventions in the labour market will be necessary to avoid rising unemployment. In this paper, we make use of a Kaleckian autonomous demand-led growth model to analyse the dynamic stability of the labour market in a zero-growth economy (ZGE) with productivity growth. In the model, net investment responds to deviations of capacity utilization from target utilization in the short run while in the long run it adjusts to firms' sales growth expectations determined by the growth rate in autonomous government expenditures. Hence, in the long run, the growth rate of the system is determined by the autonomous growth rate of government expenditures - set equal to zero - and the rate of capacity utilization converges towards the normal rate of capacity utilization. We examine the conditions under which the long-run convergence leads to a stable employment rate. In the basic model, we consider the feedback effects between productivity, distribution, and employment. However, the long-run conditions necessary for a stable employment rate are not met, suggesting, as already pointed out by ecological economists and several post-Keynesians, that policy interventions might be necessary for the stability of the labour market in a ZGE. Therefore, we consider whether the government can stabilize the labour market through a policy of working time reduction (WTR). Our findings suggest that a stable employment rate is possible in our model as long as the negative effect that labour productivity growth has on the employment rate is compensated for by the reduction in working hours.
Keywords: E24; Q01; O44; 330; zero-growth economies; socio-ecological transition; labour market stability; working time reduction